Designing an English reading instructional model incorporating Islamic content for Integrated Islamic High Schools - Seful Bahri; Rini Susanti Wulandari; Hendi Pratama (Universitas Islam Sultan Agung, 2026)
Reading is a fundamental language skill that plays a key role in students’ academic success, yet in faith-based schools English reading instruction often lacks integration with Islamic values and character formation. While previous studies have highlighted the need for contextualized materials, limited research has offered a systematic model that aligns English reading with Islamic content and the Emancipated Curriculum (Kurikukum Merdeka). This study therefore aimed to design, validate, and evaluate an English reading instructional model that incorporates Islamic themes and the ten Muwashafat. Employing a Research and Development (R&D) design using the ADDIE framework, the study involved English teachers and students at an Integrated Islamic Senior High School in Semarang, Indonesia. Data were gathered through collaborative classroom action research (CAR) combining questionnaires, observations, interviews, and pre/post tests. The model produced includes a conceptual framework, syllabus, lesson plans, and Islamic-themed reading texts structured through the IMPACT sequence (Initiate, Map, Perceive, Analyze, Construct, Think back). Expert evaluation confirmed its feasibility with average ratings of 3.53–3.67, while classroom implementation demonstrated effectiveness, as students’ reading scores increased from 6.8 (pre-test) to 7.8 (post-test), alongside positive improvements in engagement, classroom climate, and character development. The findings conclude that integrating Islamic content with character-based values strengthens English reading instruction in faith-based contexts, and future researchers are encouraged to adapt and expand the model across diverse educational settings.